1990
DOI: 10.1177/074873049000500101
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Oscillator Circadian System of Tree Shrews (Tupaia belangeri) and Its Response to Light and Dark Pulses

Abstract: The wheel-running activity rhythm of tree shrews (tupaias; Tupaia belangeri) housed in constant darkness (DD) phase-advanced following a 3-hr light pulse at circadian time (CT) 21. Dark pulses of 3 hr presented to tupaias in bright constant light (LL) did not induce significant phase shifts of the free-running activity rhythm, irrespective of the CT. In dim LL, tupaias showed simultaneous splitting of their circadian rhythm of wheel-running activity, nest-box activity, and feeding behavior. Light pulses of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…These exceptions further support the idea that circadian rhythms are under the control of at least two distinct circadian oscillators, one food-entrainable and the other light-entrainable (Pittendrigh & Daan 1976a, b, Mistlberger & Rechtschaffen 1984, Meijer et al 1990). This is emphasized by experiments with rats which show that the pre-feeding activity does not suppress the activity peak induced by light/dark alternation, even in constant lighting (Coleman et al 1982, Stephan 1986a) and for blinded animals (Gibbs 1979).…”
Section: Speciesmentioning
confidence: 56%
“…These exceptions further support the idea that circadian rhythms are under the control of at least two distinct circadian oscillators, one food-entrainable and the other light-entrainable (Pittendrigh & Daan 1976a, b, Mistlberger & Rechtschaffen 1984, Meijer et al 1990). This is emphasized by experiments with rats which show that the pre-feeding activity does not suppress the activity peak induced by light/dark alternation, even in constant lighting (Coleman et al 1982, Stephan 1986a) and for blinded animals (Gibbs 1979).…”
Section: Speciesmentioning
confidence: 56%
“…Pittendrigh and Daan (1976) were the first to systematically describe this phenomenon in hamsters and called it "splitting," citing it as evidence that the rodent circadian clock must be a complex pacemaker consisting of 2 mutually coupled oscillators. Further experimental analyses revealed that circadian rhythms of drinking (Shibuya et al, 1980), body temperature (Pickard et al, 1984), and luteinizing hormone secretion (Swann and Turek, 1985) could also split and that the 2 oscillators underlying the split state appeared to be functionally equivalent (Lees et al, 1983;Boulos and Morin, 1985;Meijer et al, 1988;Meijer et al, 1990). Pickard and Turek (1982) suggested that the split oscillators might correspond to the left and right sides of the bilaterally paired SCN, based on their observation that unilateral SCN lesions in split hamsters abolished behavioral splitting and produced a single bout of locomotion.…”
mentioning
confidence: 99%
“…Recent studies, however, have compromised this concept and show that the two putative oscillators underlying the split condition correspond to the left and right sides of the paired SCN (Meijer et al, 1990 ;De la Iglesia et al, 2000), and that splitting is not a result of changes in the relative phasing of the circadian oscillators. Some authors even suggest that the site of rhythm splitting is somewhere outside the SCN (Abe et al, 2001).…”
Section: (2 ) Biological Clocks and Oscillatorsmentioning
confidence: 94%
“…Morin, 1994 ;Hastings et al, 1995). Marked circadian fluctuations in spontaneous firing activity in the SCN have been demonstrated in vivo and in acutely dissected SCN slices (see Meijer et al, 1990;Shirakawa et al, 2001). More than half of the spontaneous firing SCN neurons show a circadian rhythm with high firing rates and more depolarized membrane potential during the subjective day.…”
Section: Neuronal Organization Of the Biological Clockmentioning
confidence: 96%